The genetics of progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) - de Silva, Rohan (Henry Stewart Talks, 2014)
PSP and CBD, Genetic risk versus inherited gene defects, tauopathies, tau pathology, role and dysfunction of tau, tau gene expression and splicing, inherited tau mutations and frontotemporal dementia, the tau gene H1 haplotype, Functional basis of association of H1 with neurodegeneration, Antiphospholipid antibodies and atherosclerosis, Other genetic associations implicating myelination and white matter changes and endoplasmic reticulum stress response